PENGARUH PENGGUNAAN MODEL PAIR CHECKS TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS X SMA NEGERI 1 KECAMATAN LAREH SAGO HALABAN - Zainur Huda; Adi Warma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to describe the effect of using the Pair Checks Model on Students' Writing Description Text Skills. This type of research is quantitative research with experimental methods. The population in this study amounted to 257 students and a sample of 50 students which was divided into two classes, the experimental class and the control class. The sampling method is using purposive sampling. The instrument in this study used a performance test with aspects of assessing the structure of the description text, the characteristics of the descriptive text, and the linguistic aspects of the descriptive text. Data analysis shows that the Pair Checks model has an effect on learning to write descriptive text on Indonesian subjects in the experimental class. This is evidenced by an increase in student scores, which at the time of the pretest the mean value ( X) was 77.6. After applying the Pair Checks learning model (pairs checking) in the learning process at the post-test time, the average value ( X) is 83.64. This can be seen from the results of the comparison of tcount with ttable (2.531 > 2.021), because tcount is greater than ttable then Ha (alternative hypothesis) is accepted. So, it can be concluded that the learning outcomes of the experimental class students who were taught using the Pair Checks learning model were better than the learning outcomes of the control class students who were taught using conventional methods.Keywords: model, pair checks, writing descriptive text